Experiences and challenges encounter among female academics during Covid-19 pandemic: a systematic review - Jamaludin, Thandar Soe @ Sumaiyah; Nurumal, Mohd. Said; Mohd Zahir, Nursyafini; Mohd Ridzwan, Mohd Danish Fu; Che Hasan, Muhammad Kamil; Sutrisno, Resti Yulianto (IIUM Press, 2023)
The declaration of COVID-19 as a pandemic demonstrated the extent of virus contamination worldwide. The pandemic made people in dilemma. The COVID-19 pandemic gave off a huge impact towards face-to-face or physical learning and the world now is going to virtual online learning and teaching until this pandemic settles down. In the academic sector, academics are challenged by virtual teaching to deliver lectures and determine the most effective method. This systematic review aimed to identify the available studies on experiences and challenges encountered among female academics during Covid-19. Searching the literature was systematically done using the PRISMA flow diagram, and the inclusion and exclusion criteria of the study were set prior to the literature search. The quality assessment was conducted by using the CASP and MMAT. There are five themes synthesised from the 21 articles included in this study. Those are experiences encountered by female academics as a mother, challenges encountered by academics as women, impacts of the Covid-19 pandemic on academic females, opinions from academicians on Distance Education during Covid-19, and strategies, coping mechanisms and solution to overcome the barriers among female academics. This study recommended for the faculty and university have a serial discussion on how to increase the effectiveness of online teaching. Beforehand, a feedback survey can be given to the female academics to analyse their current condition such as insufficient technology or standardized guidance for them to enhance online teaching. It was advisable to review the calibre and efficacy of the teaching modalities and infrastructure for the academics, even though the university had previously provided the guidelines for online teaching.